Absence of CCR2 reduces spontaneous intestinal tumorigenesis in the ApcMin/+ mouse model. Issue 10 (16th February 2021) - Jala, Venkatakrishna Rao; Bodduluri, Sobha Rani; Ghosh, Sweta; Chheda, Zinal; Singh, Rajbir; Smith, Michelle E.; Chilton, Paula M.; Fleming, Christopher J.; Mathis, Steven Paul; Sharma, Rajesh Kumar; Knight, Rob; Yan, Jun; et al.
Abstract: The biological activities of chemokine (C‐C motif) ligand 2 (CCL2) are mediated via C‐C chemokine receptor‐2 (CCR2). Increased CCL2 level is associated with metastasis of many cancers. In our study, we investigated the role of the CCL2/CCR2 axis in the development of spontaneous intestinal tumorigenesis using the Apc Min/+ mouse model. Ablation of CCR2 in Apc Min/+ mice significantly increased the overall survival and reduced intestinal tumor burden. Immune cell analysis showed that CCR2 −/− Apc Min/+ mice exhibited significant reduction in the myeloid cell population and increased interferon γ (IFN‐γ) producing T cells both in spleen and mesenteric lymph nodes compared to Apc Min/+ mice. The CCR2 −/− Apc Min/+ tumors showed significantly reduced levels of interleukin (IL)‐17 and IL‐23 and increased IFN‐γ and Granzyme B compared to Apc Min/+ tumors. Transfer of CCR2 +/+ Apc Min/+ CD4 + T cells into Rag2 −/− mice led to development of colitis phenotype with increased CD4 + T cells hyper proliferation and IL‐17 production. In contrast, adoptive transfer of CCR2 −/− Apc Min/+ CD4 + T cells into Rag2 −/− mice failed to enhance colonic inflammation or IL‐17 production. These results a suggest novel additional role for CCR2, where it regulates migration of IL‐17 producing cells mediating tumor‐promoting inflammation in addition to its role in migration of tumor associated macrophages. Abstract : What's new? Chronic inflammation is a well‐known promoter of colon cancer. Although CCR2 is a critical chemokine receptor for the recruitment of macrophages to inflammatory sites, its role in the migration of tumor‐infiltrating immune cells remains unclear. Here, in the Apc Min/+ mouse model for spontaneous intestinal tumorigenesis, CCR2 ablation increased overall survival, reduced intestinal tumor burden, and decreased IL‐17‐producing CD4+ T cells. Furthermore, lack of CCR2 in Apc Min/+ CD4 + T cells reduced IL‐17 expression and led to insufficient numbers to promote colonic inflammation. Altogether, the results suggest a novel role for CCR2 in regulating IL‐17‐producing CD4+ T cells to promote intestinal tumorigenesis.